2018
DOI: 10.1186/s40560-018-0291-y
|View full text |Cite
|
Sign up to set email alerts
|

Hypomagnesemia in critically ill patients

Abstract: BackgroundMagnesium (Mg) is essential for life and plays a crucial role in several biochemical and physiological processes in the human body. Hypomagnesemia is common in all hospitalized patients, especially in critically ill patients with coexisting electrolyte abnormalities. Hypomagnesemia may cause severe and potential fatal complications if not timely diagnosed and properly treated, and associate with increased mortality.Main bodyMg deficiency in critically ill patients is mainly caused by gastrointestinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
121
1
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(131 citation statements)
references
References 127 publications
3
121
1
6
Order By: Relevance
“…The incidence seems to highly variable across numerous studies, ranging from 14% to 61%. 4 In this study the incidence was high as 53%, which is similar to the incidence as shown in study by Singhi et al, who found a prevalence of 60%. 5 Male gender showed a preponderance to hypomagnesemia as compared to females as shown by several other studies as well.…”
Section: Discussionsupporting
confidence: 89%
“…The incidence seems to highly variable across numerous studies, ranging from 14% to 61%. 4 In this study the incidence was high as 53%, which is similar to the incidence as shown in study by Singhi et al, who found a prevalence of 60%. 5 Male gender showed a preponderance to hypomagnesemia as compared to females as shown by several other studies as well.…”
Section: Discussionsupporting
confidence: 89%
“…It is also possible that diuresis, associated with polyionic fluid administration via i.v. and NGT routes, may have contributed to increased renal loss of calcium and magnesium [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…It is required for energy production, oxidative phosphorylation, and glycolysis, and it aids in the development of the skeletal system. Mg is also necessary for the synthesis of DNA, RNA, and the antioxidant, glutathione [5,6]. In patients with normal renal function, Mg is filtered in the glomerulus.…”
Section: Introductionmentioning
confidence: 99%